PENGARUH SISTEM INFORMASI AKUNTANSI, LITERASI KEUANGAN TERHADAP KOMPETENSI PENGURUS BUMG - Himansi, Muhammad Rendy Alkhobir; Tuti Meutia; Mayang Murni (Jurnal Mahasiswa Akuntansi Samudra, 2025)
The purpose of the research that the author wants to achieve is to determine the influence of accounting information systems on the competence of BUMG administrators in Langsa Baro District. To find out the influence of financial literacy on the competence of BUMG administrators in Langsa Baro District. To find out the influence of accounting information systems and financial literacy on the competence of BUMG administrators in Langsa Baro District. The scope of the research discusses the influence of accounting information systems and financial literacy on the competence of BUMG administrators in Langsa Baro District. The type of data used in this study is quantitative data. The sample in this study is 48 respondents. The data analysis method used in this study is quantitative descriptive analysis using the help of the SPSS 25.0 statistical application. The results of the research are accounting information systems, financial literacy simultaneously has a significant effect on competence. Partially, the accounting information system has a significant negative effect on competence, but financial literacy has a positive and significant effect on the competence of BUMG administrators in Langsa Baro District. The limitation of this study is that this research is only carried out based on the location that can be reached by the researcher, so it is felt that the distribution of the questionnaire is not widespread. The data collection method carried out in this study is in the form of primary data and disseminated through questionnaires directly and online, but in its implementation there are still respondents who do not understand the content of the questionnaire. This research is limited to using only the variables of digital economy implementation, availability of working capital and financial literacy. The suggestions that can be given are that this research uses a data collection method through questionnaires distributed to respondents in each village in the Langsa Baro area. In the study, the number of samples that could be studied was only 48 questionnaires after the research instrument test was carried out. For the next researcher, it should be to expand the research so that more complete information about accounting information systems, financial literacy to competencies is obtained.